2020
DOI: 10.1186/s12985-020-01450-7
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant pseudorabies virus expressing African swine fever virus CD2v protein is safe and effective in mice

Abstract: Background African swine fever (ASF) leads to high mortality in domestic pigs and wild boar and is caused by the African swine fever virus (ASFV). Currently, no vaccine is commercially available for prevention, and the epidemic is still spreading. Here, we constructed a recombinant pseudorabies virus (PRV) (PRV-ΔgE/ΔgI/ΔTK-(CD2v)) that expresses the CD2v protein of ASFV and evaluated its effectiveness and safety as a vaccine candidate in mice. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 54 publications
(82 reference statements)
2
29
0
Order By: Relevance
“…PRV is a model organism for studying the molecular pathogenesis of herpesviruses, including the mechanism of neurotropism [6,7] and the regulation of gene expression. PRV also serves as a model for the development of genetically engineered vaccines [8].…”
Section: Introductionmentioning
confidence: 99%
“…PRV is a model organism for studying the molecular pathogenesis of herpesviruses, including the mechanism of neurotropism [6,7] and the regulation of gene expression. PRV also serves as a model for the development of genetically engineered vaccines [8].…”
Section: Introductionmentioning
confidence: 99%
“…PRV is a model organism for studying the molecular pathogenesis of herpesviruses, including the mechanism of neurotropism [6,7] and the regulation of gene expression. PRV is also served as a model for the development of genetically engineered vaccines [8]. Additionally, this virus is the most popular multisynaptic tracer of Direct RNA sequencing generates less false transcripts, but it produces incomplete reads since 15-30 bp sequences always lack from the 5'-termini, and in many cases poly(A) tails are also missing.…”
Section: Introductionmentioning
confidence: 99%
“…However, due to the different situations in vitro and in vivo, it is worthwhile to detect and compare the expression of the three recombinant viruses in vivo in further studies. A previous study has shown that the viral genome DNA was detected in the brain, heart, lung, liver, kidney, and spleen tissues of PRV-Fa infected mice, but not in PRV-ΔgE/ΔgI/ΔTK infected group at 72 h post infection [ 6 ]. When the infection time was extended to 200 h, viral DNA was detected in the brain and lungs of mice infected with PRV-ΔgE/ΔgI/ΔTK.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we generated a TK&gE-deleted PRV (PRV Δ TK&gE−AH02 ), which is safe for 1-day-old piglets with maternal PRV antibodies and 4 ~ 5 week-old PRV antibody negative piglets and can provide complete protection in weaned pigs against challenged with virulent AH02LA strain at 7 days post vaccination [ 4 ]. Several previous reports have shown that recombinant PRVs expressing foreign antigens are able to stimulate humoral and cell-mediated immune responses against both PRV and other viruses [ 5 , 6 ]. Thus, PRV Δ TK&gE−AH02 might be a technically appropriate vector for the expression of foreign antigens of other swine diseases.…”
Section: Introductionmentioning
confidence: 99%